(3eYQGL GdfHj Udi Gddg Ydjg hSde QhGjI GHf YHGSs - (3GdbQTj GdgGTej, GHf YHGS, YHO Gddg Hf YHGS Hf YHO GdeWdH, J(B68(3g`s ((3GdSjO MSf Hf YeQs)
(3ChdgG (B:s
(3cJGH ajg MOjK GdeYQGL hGdESQGA HSjO GdeQSdjf ef GdeSLO GdMQGe Edi HjJ GdebOS hUYhOg hQLhYg Edi aQGTg aj djdI hGMOIs
(3BNQgG (B:s
(3hGdMjGJ hGdYbGQH dCYOGFg hfSCd Gddg GdSdGeI aj GdOGQjf ef GdfGQ HLGg eMeO GdeNJGQ hBdg hCUMGHg GdCNjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 95s
(3eYLe GdeDdajf(B: 2 / 249s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs